"Awake" Spinal Cord Monitoring Under Local Anesthesia and Conscious Sedation in Fenestrated and Branched Endovascular Aortic Repair. (December 2021) - Abisi, Said; Musto, Liam; Lyons, Oliver; Carmichael, Michelle; Sallam, Morad; Gkoutzios, Panos; Zayed, Hany; Puchakayala, Madhusudan
Introduction: Endovascular repair of thoracoabdominal aortic aneurysms carries a risk of spinal cord ischemia, the causes of which remain uncertain. We hypothesized that local anesthesia (LA) with conscious sedation could abrogate the potential suppressive cardiovascular effects of general anesthesia (GA) and facilitate intraoperative monitoring of neurological function. Here, we examine the feasibility of this technique during fenestrated (FEVAR) or branched endovascular aortic repair (BEVAR). Materials and Methods: Consecutive patients undergoing FEVAR or BEVAR under LA and conscious sedation by a team at a single center were analyzed. Patients received conscious sedation using intravenous remifentanil and propofol infusions in conjunction with a local anesthetic agent. No patient had a prophylactic spinal drain inserted. Outcome measures included conversion to GA, need for vasopressors and/or spinal drainage, length of stay, complications, and patient survival. Results: A total of 44 patients underwent FEVAR or BEVAR under LA and conscious sedation. The cohort included thoracoabdominal aortic aneurysms (n=41) and pararenal aneurysms treated with endografts covering the supraceliac segment (n=3). Four patients (9%) required conversion to GA at a median operative duration of 198 minutes (range 97–495 minutes). Vasopressors were required intraoperatively in 3 of the cases that were converted to GA. No patient developed spinal cord ischemia and none had insertion of a spinal drain. The median hospital length of stay was 4 days (range 2–41 days). Postoperative delirium and hospital-acquired pneumonia was seen in 7% of patients. All patients survived to 30 days, with 95% alive at a median follow-up of 15 months (range 3–26 months). Conclusion: LA and conscious sedation is a feasible anesthetic technique for the endovascular repair of thoracoabdominal aortic aneurysms.